Kształtowanie się idei narodowej w literaturze białoruskiej XIX wieku - Wasiluk, Joanna (Acta Polono-Ruthenica, 2012)
The article is about shaping of the national idea in the period of forming the new Byelorus- sian literature (XIX century). Mainly the role of folklore in this process is taken into consideration. Studying the literary legacy of the member of Filomaci and Filareci association Jan Czeczot there is analysis of Lithuanian contribution of the Byelorussian literature into Byelorussian renaissance (W. Konan). The most important book of the representative of Byelorussian trend Jan Barszczew- ski called Szlachcic Zawalnia albo Białoruś w opowiadaniach fantastycznych is examined.The contribution into the development of the Byelorussian national idea of Franciszk Bahuszewicz, the author of preface to Dudka białoruska manifesto of Byelorussian renaissance is emphasized. His composition becomes the impulse to the further development of Byelorussian literature and to the forming of the Byelorussian national idea.